Crystal structure and mechanical properties of nickel–cobalt alloys with different compositions: A first-principles study. (February 2020) - Liu, Peng; Chen, Dengfu; Wang, Qinzheng; Xu, Pei; Long, Mujun; Duan, Huamei
Abstract: The properties of nickel–cobalt alloys depend greatly on their composition. In this study, we investigated the crystal structure and mechanical properties (elastic properties and hardness) of nickel–cobalt alloys with different compositions based on first-principles calculations. The formation enthalpy (Δ H ) values were calculated and the results showed that as the cobalt content increased in the alloys, the crystal structure of the alloys changed from face centered cubic (fcc) to hexagonal close-packed (hcp), and a coexistence zone with both the fcc and hcp phases existed when the cobalt content was 50–80 at.%. The formation enthalpy values for the fcc-phase and hcp-phase were equal when the cobalt content was 65.5 at.%. The results were in good agreement with the experimental results. Calculations of the elastic properties showed that increasing the cobalt content of the alloys could increase the stiffness as well as improving the compression and shear resistance, but the ductility was reduced. The hardness increased for the fcc and hcp phases as the cobalt content increased. When the cobalt content was 50 at.%, the hardness reached the maximum value of 1032 HV. Further analyses of the electron localization function demonstrated that the increases in the compression and shear resistance, stiffness, and hardness of the nickel–cobalt alloys as the cobalt increased could be attributed to the enhanced covalent bonds between Ni–Co and Co–Co atoms. Highlights: Structure of Ni–Co alloys changes from fcc to hcp as cobalt content increases. fcc and hcp phases coexist at cobalt contents of 50–80 at.%. Formation enthalpy same for fcc-phase and hcp-phase at cobalt content of 65.5 at.%. Stiffness, hardness, and compression/shear resistance enhanced by high Co content. Improved mechanical properties due to enhanced covalent bonds between Ni–Co and Co–Co.